A new control strategy for low-voltage ride-through of three-phase grid-connected PV systems - Meghdad Fazeli (The Journal of Engineering, 2019)
Power quality and current limitation are the most important aspects of the grid-connected power converters under fault. Since the distributed energy resources are widely used, fault management strategy is important for micro-grids applications. This paper presents a new control strategy for low-voltage ride-through for 3-phase grid-connected photovoltaic systems. The proposed method, which is designed in a synchronous frame using positive and negative sequence components, can protect the inverter from overcurrent failure under both symmetrical and unsymmetrical faults and provides reactive power support. The method does not require a hard switch to switch from MPPT to a non-MPPT algorithm, which ensures a smooth transition.